Mechanistic insights into the more potent effect of KP-54 compared to KP-10 in vivo. - Xavier d'Anglemont de Tassigny; Channa N Jayasena; Kevin G Murphy; Waljit S Dhillo; William H Colledge (PLoS ONE)
Kisspeptins regulate the mammalian reproductive axis by stimulating release of gonadotrophin releasing hormone (GnRH). Different length kisspeptins (KP) are found of 54, 14, 13 or 10 amino-acids which share a common C-terminal 10-amino acid sequence. KP-54 and KP-10 have been widely used to stimulate the reproductive axis but data suggest that KP-54 and KP-10 are not equally effective at eliciting reproductive hormone secretion after peripheral delivery. To confirm this, we analysed the effect of systemic administration of KP-54 or KP-10 on luteinizing hormone (LH) secretion into the bloodstream of male mice. Plasma LH measurements 10 min or 2 hours after kisspeptin injection showed that KP-54 can sustain LH release far longer than KP-10, suggesting a differential mode of action of the two peptides. To investigate the mechanism for this, we evaluated the pharmacokinetics of the two peptides in vivo and their potential to cross the blood brain barrier (BBB). We found that KP-54 has a half-life of ~32 min in the bloodstream, while KP-10 has a half-life of ~4 min. To compensate for this difference in half-life, we repeated injections of KP-10 every 10 min over 1 hr but failed to reproduce the sustained rise in LH observed after a single KP-54 injection, suggesting that the failure of KP-10 to sustain LH release may not just be related to peptide clearance. We tested the ability of peripherally administered KP-54 and KP-10 to activate c-FOS in GnRH neurons behind the blood brain barrier (BBB) and found that only KP-54 could do this. These data are consistent with KP-54 being able to cross the BBB and suggest that KP10 may be less able to do so.